Pien-tze-huang promotes wound healing in streptozotocin-induced diabetes models associated with improving oxidative stress via the Nrf2/ARE pathway - Liu, Ying; Mo, Jiake; Liang, Fang; Jiang, Siwei; Xiong, Jing; Meng, Xubiao; Mo, Zhaohui (Frontiers in Pharmacology, 2023)
Diabetic foot ulcers are a serious complication of diabetes, with high mortality and a lack of effective clinical treatment, which leads to a considerable financial burden. Pien-Tze-Huang (PZH) is a Chinese traditional medicine with a long history that has been found to be an effective and convenient treatment for inflammatory diseases such as skin abscesses and ulcers. In this study, we assessed the effects of PZH on diabetic wounds and the underlying mechanisms. The wounds were established on the backs of streptozotocin-induced type 1 diabetic rats and type 2 diabetic mouse models. We found that PZH treatment used locally or by gavage significantly promoted wound healing, accelerated re-epithelialization and vasculature in the wound tissue, upregulated the expression of the growth factors VEGF, PDGF, and EGF, and activated the Nrf2/ARE pathway in the wound tissue. In vitro assays showed that PZH improved the proliferation of human umbilical vein endothelial cells (HUVECs) cultured in palmitic acid, reduced the expression of the apoptotic proteins p53, Bax, and cleaved-caspase3, and activated Nrf2/ARE signaling; however, these protective effects were abrogated after Nrf2 was knocked down by specific siRNA. In addition, the levels of the serum inflammatory cytokines IL-1β, TNF-α, and IL-6 were reduced after PZH gavage treatment. In conclusion, the positive role of PZH in diabetic wound healing might be related to the activation of the Nrf2/ARE pathway to regulate the level of oxidative stress in vivo and increase the expression of growth factors to improve angiogenesis.